PENDIDIKAN MULTIKULTURAL DALAM PEMBELAJARAN AKIDAH AKHLAK: SEBUAH DESAIN KURIKULUM UNTUK MI - Ilya, Ilya; Wahyuni, Sri (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This research is motivated by the gap between the reality of multicultural Indonesian society and the Akidah Akhlak curriculum in Madrasah Ibtidaiyah (MI), which tends to focus on cognitive understanding and has not optimally instilled the values of tolerance. The focus of this research is to design a multicultural Akidah Akhlak curriculum development design for MI, which aims to shape characters who not only understand Islamic teachings but are also able to live harmoniously in diversity. As a crucial step, this research uses descriptive qualitative methods through literature studies and curriculum analysis to develop an integrated learning framework. The main finding of this research is a curriculum design that explicitly integrates multicultural values—such as tolerance and respect for differences—into each basic competency, by prioritizing a deep learning approach, a cooperative learning model, and a holistic evaluation system. In conclusion, this multicultural Akidah Akhlak curriculum design is a strategic step to shape a generation of faithful, noble, and inclusive Muslims from an early age, as an answer to the urgent need for Islamic education in the context of a pluralistic society. ABSTRAKPenelitian ini dilatarbelakangi oleh adanya kesenjangan antara realitas masyarakat Indonesia yang multikultural dengan kurikulum Akidah Akhlak di Madrasah Ibtidaiyah (MI) yang cenderung masih berfokus pada pemahaman kognitif dan belum optimal menanamkan nilai-nilai toleransi. Fokus penelitian ini adalah merancang desain pengembangan kurikulum Akidah Akhlak multikultural untuk siswa MI, yang bertujuan membentuk karakter yang tidak hanya memahami ajaran Islam, tetapi juga mampu hidup harmonis dalam keberagaman. Sebagai langkah penting, penelitian ini menggunakan metode kualitatif deskriptif melalui studi pustaka dan analisis kurikulum untuk menyusun sebuah kerangka pembelajaran yang terintegrasi. Temuan utama dari penelitian ini adalah sebuah rancangan kurikulum yang secara eksplisit mengintegrasikan nilai-nilai multikultural—seperti toleransi dan menghargai perbedaan—ke dalam setiap kompetensi dasar, dengan mengedepankan pendekatan deep learning, model pembelajaran kooperatif, serta sistem evaluasi holistik. Kesimpulannya, desain kurikulum Akidah Akhlak multikultural ini merupakan langkah strategis untuk membentuk generasi Muslim yang beriman, berakhlak mulia, dan inklusif sejak dini, sebagai jawaban atas kebutuhan mendesak pendidikan Islam dalam konteks masyarakat yang majemuk.